Formulation of Hypopigmentation Cream and Evaluation of its Effect on Skin Pigment. Part I: Formulation of the Product - Amina Hamed Alobaidi; Eqbal Salih Hamad; Kudair Abas Kudair; Abdulghani Mohamed Alsamarai (Our Dermatology Online, 2014)
Melasma is a commonly acquired hypermelanosis of facial skin due to various etiological factors including hormonal imbalance. Although it affects any one is particularly common in women, especially pregnant women and those who taking oral or patch contraceptives or hormone replacement therapy. This research aimed to formulate stable water in oil (w/o) cream containing plant extract of Glycyrrhiza glabra as active material obtained by concentrating the alcoholic extract of the plant roots, was entrapped in the inner aqueous phase of w/o cream. Base containing no active material and a formulation containing ethanolic extract of the plant which was prepared in Samarra Drugs Industry laboratories. Samples of base and formulation were stored at different accelerated conditions (8°C, 25°C, 30°C, 40°C, 40°C +75% RH) for four weeks to predict the stability of the creams. It was concluded that the formulation was stable chemically and physically over the studied storage conditions and without induction of allergic or contact dermatitis.